Percutaneous left atrial appendage closure in AF using Amplatzer Cardiac Plug: First single center experience from India - Ranjan K. Shetty (Indian Heart Journal, 2015)
Background: Atrial fibrillation (AF) is one of the most common arrhythmias accounting for significant mortality and morbidity, especially in elderly. Though oral anticoagulation (OAC) is an effective mode of prevention of stroke in patients of AF, bleeding complication remains a major concern. Because of these issues, a significant proportion of patients either does not receive or receive suboptimal doses of OAC. Methods: In such patients, percutaneous left atrial appendage (LAA) closure remains an interesting option. Experience and literature of this procedure from India have been sparse. We report the first single center experience, from India, of percutaneous LAA closure with Amplatzer Cardiac Plug in 10 patients of non-valvular AF. These patients had contraindications for OAC or had high risk of bleeding or labile international normalized ratio (INR) on therapy. Results: We successfully deployed the devices in all of the cases with no major complications perioperatively and on short-term follow-up. We also report a comprehensive review on the technique of percutaneous LAA closure using Amplatzer Cardiac Plug, including some novel modification with our experience of doing percutaneous mitral balloon valvuloplasty.